Peran Pesantren dalam Pendidikan Karakter di Era Globalisasi - Mita Silfiyasari; Ashif Az Zhafi (Program Pascasarjana Universitas Ibrahimy, 2020)
This article describes the role of an Islamic boarding school in character education in the era of globalization. This article used a literature research approach. In this research, Islamic boarding school had been able to have a role in the students’ character building supported by the main figure who is a Kiai. It can not be separated from the role of a teacher/Kiai in producing students who have noble character. The role of Islamic boarding school in character education is Islamic boarding school as guardian and preserver of religious values; Islamic boarding school as the innovator of religious understanding; and as inspirer, motivator, and dynamist of development implementation at the local and regional levels.